Answer: see proof below
Explanation:
Use the following when solving the proof...
Double Angle Identity: cos2A = 1 - 2sin²B
Pythagorean Identity: cos²A + sin²A = 1
note that A can be replaced with B
Proof from LHS → RHS
Given: cos²A + sin²A · cos2B
Double Angle Identity: cos²A + sin²A(1 - 2sin²B)
Distribute: cos²A + sin²A - 2sin²A·sin²B
Pythagorean Identity: 1 - 2sin²A·sin²B
Pythagorean Identity: cos²B + sin²B - 2sin²A·sin²B
Factor: cos²A + sin²B(1 - 2sin²A)
Double Angle Identity: cos²B + sin²B · cos2A
cos²B + sin²B · cos2A = cos²B + sin²B · cos2A